Pengaruh Laju Aerasi Terhadap Produksi Kitinase Oleh Trichoderma Asperellum TNJ63 - Riko Naldo Saputra; Sri Helianty; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chitinase is enzyme that hydrolyze chitin compound in β-1,4-N-acetyl-glucosamine into monomer N-acetyl-glucosamine, which widely occurs in nature. This enzyme is potentially applicable in the field of pharmaceuticals for the treatment of cancer, tuberculosis, asthma, diabetes, allergies and infections. Chitinase can be produced by microorganisms chitinolytic are numerous in the biosphere, one of the local isolates Trichoderma asperellum TNJ63. In this research, scale up production of 25 mL to 1.5 L medium. Fermentation was carried out in a 2 L stirred tank bioreactor using methods submerged fermentation (SmF) with the substrate chitin from shrimp shells. Chitinase production conducted for 9 days with stirring speed of 40-60 rpm, and the effect of aeration rates (0 vvm; 0.5 vvm; 1 vvm and 1.5 vvm) studied the chitinase activity produced. The highest chitinase activity was obtained at 1 vvm aeration rate and fermentation time of 7 days with 0.0160 U / mL through analysis UV-Vis spectrophotometer with a sugar analysis method, Nelson-Somogyi.Keywords: aeration, chitinase, scale up, shrimp shells, Trichoderma asperellum TNJ63